RTHP-11. THE EFFECT OF PRESCRIPTION ISODOSE LINE ON LOCAL CONTROL AND RADIOGRAPHIC RESPONSE IN GAMMA KNIFE RADIOSURGERY OF VESTIBULAR SCHWANNOMA. (11th November 2019) - Teyateeti, Achiraya; Graffeo, Christopher; Perry, Avital; Brown, Paul; Pollock, Bruce; Michael, Link
Abstract: Traditionally, the 50% isodose line (IDL) is used for prescription dose when vestibular schwannomas (VS) are treated with Gamma Knife radiosurgery (GKRS). To compare the effect of IDL on treatment outcomes, propensity score-matched analysis according to age at time of GKRS and tumor volume (TV) between cohorts treated at 40%IDL and 50%IDL was performed. Patients with no history of neurofibromatosis, GKRS prescribed marginal dose of 12–14 Gy and TV ≤ 10 cc were identified. Patients were excluded if follow-up time was < 2 years. Eventually, 30 and 28 patients were included in 40%IDL and 50%IDL cohorts, respectively. Mean age and TV were not significantly different between 40%IDL and 50%IDL groups; 54.5 versus 54.0 years (p=0.891) and 2148.61 versus 2031.10 mm 3 (p=0.844), respectively. Median prescription dose was 12 Gy in both groups. At median follow-up times of 111 and 72 months, the 2, 5 and 10-year local control were 100%, 96.4% and 96.4% for 40%IDL and 96.4%, 86.7%, and 86.7% for 50%IDL (p=0.243), respectively. Among 40 patients with accessible follow-up MRIs (40%IDL-n=19, 50%IDL-n=21), volume reduction at last follow-up MRIs and rate of reduction per year for 40%IDL and 50%IDL were 48.1% versus 38.3% (p=0.05) and 5.5% versus 6% (p=0.749), respectively. Of 21 patients with serviceable hearing prior to GKRS and available audiograms after GKRS (40%IDL-n=8, 50%IDL-n=13), the 2, 5 and 10-year hearing preservation rate were 100%, 83.3% and 62.5% for 40%IDL versus 76.2%, 57.1% and 11.4% for 50%IDL (p=0.017). Facial paresthesia, facial palsy and ataxia/gait disturbance requiring steroid and/or shunt were lower in 40%IDL compared to the 50%IDL; 6.7% versus 17.9% (p=0.208) and 3.3% versus 7.1% (p=0.532). To summarize, VS treated at 40%IDL have slightly better local control, although not statistically significant, compared to tumors treated at 50%IDL. However, hearing preservation and safety seem to be more favorable toward 40%IDL group.